PENGARUH PENERAPAN METODE BERMAIN PERAN (ROLE PLAY) TERHADAP PEMAHAMAN PERILAKU BULLYING PADA ANAK USIA DINI - Fatimah, Ade Siti; Ihsanda, Nu'man; Hidayat, Yusuf; Tya, Sandi (Sekolah Tinggi Agama Islam Putra Galuh Ciamis, 2024)
Bullying is an act of verbal and non-verbal physical violence committed by an early childhood to other weak early childhood and it is done repeatedly. The role play method in learning can provide an understanding of bullying behavior in early childhood, because this learning method actively involves early childhood through various roles played at which early childhood can obtain various information, so that learning would be more meaningful. This study aims to determine the influence of using the role play method on the understanding bullying behavior in early childhood. The method used in this study is a quantitative under a pre-experiment approach (one group pretest posttest design). The results of this study showed that based on the amount of t-table and t-count, those have been obtained, t-table = 12.526 > t-count = 2.160. In conclusion, there is a significant influence in using the role play method on early childhood’s understanding on bullying behavior.